Does modularizability of technology matter on the technology competition?. Issue 1 (2nd January 2018) - Park, Jinhan; Lee, Su; Chhajed, Dilip; Kim, Kilsun
ABSTRACT: The current study presents a conceptual model that explains the role of architectural characteristics of a technology on the technology competition. We argue that modularizability of a core technology can enhance adopting firms' dynamic capabilities in technology competition by influencing the shape of suppliers' networks not only within but also across industries. Furthermore, the increased possibilities of firms' participation enhance the chances of the technology to better address evolving needs of consumers in market. To coherently explain the effects of the product architectural characteristics of a technology, we explain through the conceptual model how factors such as modularizability, collaborability, expandability and addressability, interact with one another to affect the determination process of a dominant technology. To verify the construct validity of the factors, measurement items for each concept are developed and empirically tested using survey data collected from manufacturing firms across different industries. We show that a technology that is more suitable for modular product architecture exhibits better possibilities for firms' participation and cooperation by extending a supplier network both within an industry and across different industries. We also show that technologies that excel in the aforementioned fronts are more likely to accommodate evolving market needs during technology competition and to finally win the competition.